(3GdJaSjQ GdhSjWs - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj GdfjSGHhQj , J (B468 (3g` s ((3CHhHcQ Hf eMeO Hf CMeO GdSeQbfOi s)
(3ChdgG (B:s
(3adeG cGfJ CSeGA Yf MQa LGRJ ajgG GdEeGdI hHOd Ydi dCfgG eG Cf CSeGA GdYOO GPG GNJHQJ YfgG GYJHQJgG s
(3BNQgG (B:s
(3Je cJGHI GdOaJQ GdKGdK ef GdJaSjQ GdhSjW ef JUfja GdGeGe Ydi Hf CMeO GdhGMOi s
(3GdfSNI HgG MhGTs
(3jHJOF HChd ShQI eQje hjfJgi HBNQ ShQI GdReQs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B- (3GdLRA (B1 - (3U (B629 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B460s
Keywords: (3GdJaSjQ hYdhe GdbQBfs